Sentiments Organize Affect Concepts in Yasawa, Fiji: a Cultural Domain Analysis - Gervais, Matthew M. (Journal of cognition and culture, 2024)
For decades, intensive research on emotion has advanced general theories of culture and cognition. Yet few theories can comfortably accommodate both the regularities and variation empirically manifest in affective phenomena around the world. One recent theoretical model (Gervais & Fessler, 2017) aims to do so. The Attitude-Scenario-Emotion (ASE) model of sentiments specifies an evolved psychological architecture that potentiates regular variation in affective experience and behavior in lived interaction with social, ecological and normative contexts. This model holds that sentiments – functional networks of bookkeeping attitudes and commitment emotions – produce context-dependent universals in salient social-relational experiences, predictably patterning affect concepts. The present research aims to empirically evaluate implications of the ASE model of sentiments using quantitative data from 10 months of fieldwork in Indigenous iTaukei villages on Yasawa Island, Fiji. Study 1 is a series of structured interviews that aim to elicit the full breadth of the Yasawan affect lexicon. In freelists and sentence frames, Yasawans use distinct sets of terms to refer to “feelings about” particular people (attitudes), and “feelings because of” particular events (emotions). Study 2 uses a pile sort task to show that the salient features of Yasawan affective experience are social-relational dimensions of communion and power, while both HCA and MDS reveal distinct social attitudes – “love” (lomani) and “like’ (taleitaki), “respect” (dokai), “contempt” (beci), “hate” (sevaki), and “fear” (rerevaki) – anchoring the conceptual organization of Yasawan emotions. Study 3 uses hypothetical vignettes with a between-subjects attitude manipulation and Likert-style emotion ratings to show that these attitudes differentially moderate emotions across social scenarios; differences are both quantitative and qualitative; each attitude is emotionally pluripotent; and divergent attitudes (e.g., “love” and “hate”) produce the same emotions in starkly different situations – a predicted three-way interaction of attitude x scenario x emotion. These data are broadly consistent with ASE hypotheses; population variation in affective worlds may follow from differential engagement of universal attitude-emotion networks (sentiments) experienced across social, ecological and normative contexts.